(untitled) (Estudio Agustiniano, 2013)
Monotheism did not constitute the essence of the Jewish religion in its origins. The ancient Hebrew people were not monotheistic but henot- heistic: they worshipped the living God of Israel, but recognised the possibility of the existence of other gods that protected the different peoples and accompanied them through the stages of their history. The prophets, beginning with the great Elijah (9th c. BC), Amos and Hosea (8th c. BC), and then Proto-Isaiah, Jeremiah and Ezekiel (8th - 6th c. BC), contributed decisively in the move towards faith in the one and only Yahweh. But it was the Deutero-Isaiah (6th c. BC), the prophet of divine incomparability and transcendence, the greatest theological phenomenon of the First Testament, who can be considered to be the first truly monotheistic author in biblical tradition, both in the exposition of doctrinal concepts and in linguistic expression.